E-commerce : Business, technology, society - Laudon, Kenneth C. (Pearson Education, 2013)
This comprehensive, market-leading text emphasizes the three major driving forces behind e-commerce-technology change, business development, and social issues-to provide a coherent conceptual framework for understanding the field.